A Revision of the Australian species of Lynceus Müller, 1776 (Crustacea: Branchiopoda: Laevicaudata, Lynceidae) - Timms, Brian V (Zootaxa, 2013)
Australia has had two species of Lynceus, L. macleayanus (King, 1855) and L. tatei (Brady, 1886) reported to date, both poorly described and without types, and supposedly both widely distributed. This study establishes neotypes and redescribes each according to modern standards. The present distribution of each is severely restricted by the destruction of temporary aquatic habitats, both in cities and in the country and also misunderstood by the lack of recent collecting in some outlying areas. Detailed study of male first thoracopods, together with an understanding of the form of the head and rostrum, antenna 2 spinal patterns, carapace shape, and the females’ lamina abdominalis, most of which are discontinuously variable, has resulted in the delineation of four more species: L. baylyi sp. nov. in desert rockholes of Western Australia; L magdaleanae sp. nov. mainly in deep gnammas of the WA Wheatbelt and Goldfields but also extending into NT, Qld and SA; L. susanneae sp. nov. of rockholes on the Nullarbor Plain, WA; and L. argillaphilus sp. nov. of the coastal Pilbara, WA. Identification keys are provided for all six species, both males and females.